PENGARUH MODAL INTELEKTUAL DAN TINGKAT PERTUMBUHAN MODAL INTELEKTUAL TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2009-2013 (Students' Journal of Accounting and Banking, 2014)
This study aims to determine the effect of intellectual capital and intellectual capital growth rate of the company's financial performance. Intellectual Capital is the company's assets in the form of intangible assets that can be used as a corporate value creation. In Indonesia, the disclosure and reporting of intellectual capital is still limited so indirectly may mislead users of financial statements related to the company's financial performance assessment. The population in this study is a manufacturing company that is listed on the Indonesia Stock Exchange (IDX) in the period 2009 - 2013 The sample in this study were taken by purposive sampling method. Data were analyzed by using Partial Least Square (PLS). These results indicate that the variables of intellectual capital (VACA, VAHU, STVA) positive effect on performance (ROA, ATO, EPS), variable intellectual capital has positive influence on performance t + 2 (ROA_2, ATO_2, EPS_2), the variable growth of intellectual capital (ROGIG) does not affect the performance of t +2 (ROA_2, ATO_2, EPS_2).Keywords: intellectual capital, financial performance, Partial Least Square (PLS)